Pemekaran Daerah dan Terbentuknya Kelas Menengah (Baru) Papua - I Ngurah Suryawan (JSW (Jurnal Sosiologi Walisongo), 2018)
This article discusses the impact of territorial expansion on the socio-political structure among Papuans. The strategic issue of socio-economic and cultural transformation that is driven through territory expansion becomes hampered when new Papuan elites take over resources. The formation of a new social class, namely the new Papuan elites provided enormous political economy benefits in the expansion of the region. Strategic political positions and access toward development projects are tempting income. The presence of the new Papuan middle class is an important phenomenon in the midst of various development efforts for the welfare of the Papuan. Applying ethnographic approach this study aims to examine the process of the formation of Papuan elites as an impact of the dynamics of regional expansion, as well as the habitus of the presence of elites and strategy practiced in the community level.